Investment performance analysis of managerial expertise: evidence from Malaysian-based international equity unit trust funds - Low, Soo-Wah (Penerbit Universiti Kebangsaan Malaysia, 2013)
This paper evaluates the investment performance of Malaysian-based international equity funds. The results on the overall fund performance using Jensen’s (1968) model indicate that, on average, international funds have significant negative risk-adjusted returns over the study period from 2008-2010. Since the model ignores market timing activity, it implicitly attributes the overall negative return to manager’s poor stock selection ability. However, the performance breakdown results on managerial expertise using the models of Treynor and Mazuy (1966) and Henriksson and Merton (1981) show evidence of positive selectivity and negative market timing returns. Taken together, the highly significant negative timing returns suggest that, on average, international fund managers have perverse market timing ability. The paper finds little evidence that Malaysian investors achieve diversification benefits from investing in overseas equity markets.